2012
DOI: 10.1142/s2010269012500172
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Traditional Authorities and Decentralized Structures in Ghana: Conflicting Roles or a Struggle for Power and Legitimacy

Abstract: This paper uses the Wenchi District as a case study to generate a nuanced understanding of the interactive process between decentralized government structures and traditional authority in the context of Ghana's highly touted democratic achievements within the African continent. Qualitative methods involving focus group discussions of 159 males and 98 females aged between 18 to 72 years in 8 communities were used to facilitate insightful discussions and reflections. The focus group discussions (FGDs) were compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Since the advent of the local government system in Ghana, studies have found that traditional authorities have been politically, administratively and financially marginalised (Kessey 2006;Mahama 2009). Other studies have shown that in Ghana, interactions between local government units and traditional authorities are characterised by mistrust generated by competition for power and legitimacy, which tend to stifle genuine participation between the two systems of government at the district level (Taabazuing et al 2013). This finds corroboration in a study that looked at the role of the chieftaincy institution in the attainment of the Sustainable Development Goals (SDGs) in Ghana, which concluded that successful implementation of the SDGs would be faster if the chiefs are actively involved in the process and given specific roles to play (Assanful 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the advent of the local government system in Ghana, studies have found that traditional authorities have been politically, administratively and financially marginalised (Kessey 2006;Mahama 2009). Other studies have shown that in Ghana, interactions between local government units and traditional authorities are characterised by mistrust generated by competition for power and legitimacy, which tend to stifle genuine participation between the two systems of government at the district level (Taabazuing et al 2013). This finds corroboration in a study that looked at the role of the chieftaincy institution in the attainment of the Sustainable Development Goals (SDGs) in Ghana, which concluded that successful implementation of the SDGs would be faster if the chiefs are actively involved in the process and given specific roles to play (Assanful 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary Ghanaian policy frameworks accord a prominent place to chiefs in governance and community development (Ray 1996;Boafo-Arthur 2003;Schramm 2004;Abotchie et al 2006;Bob-Milliar 2009;Taabazuing et al 2012;Owusu-Mensah 2013;Neusiri 2014). The importance of chiefs is articulated within the 1992 National Constitution, which recognises chiefs as the legal custodians of land and natural resources, with rights to transact and gain specified shares of royalties from market sales of these resources.…”
Section: Discourses About Chiefs and Land Administration In Ghanamentioning
confidence: 99%
“…Elections organised in 1968 brought the Busia-led Progress Party (PP) to power, based on the alliance between business people and dominant chiefs that had characterised the NLM. After the 1966 coup, the role of traditional authorities in local government was once again strengthened, and chiefs were given the power to appoint one third of local government representatives (Ayee 1994;Taabazuing et al 2012). Chiefs also experienced fewer fetters over their control of land and gained greater freedoms to extract revenues from land.…”
Section: The Rise Of Commercial Farmers In the 1970s And Its Impact On Land Relationsmentioning
confidence: 99%
“…The effect is that the relationship between chiefs and local government authorities is at times characterised by conflict, tensions and mistrust (Turmann, 2010) thereby affecting community development. Also, some chiefs lack the capacity to efficiently represent the interest of their people and have weak social mobilisation skills (Turmann, 2010) (Ayee, 2006), partnership modalities (Dawda & Dapilah, 2013;Mahama, 2009), role of chiefs in development (Boateng et al, 2016;Boateng, 2010), the relationship between chiefs and government officials (Taabazuing et al, 2012;Brempong, 2007;Rathbone, 2000), collaboration between chiefs and local government authorities (Arthur & Dawda, 2015;Boateng & Afranie, 2020b) and the primacy of the chieftaincy institution within a democratic dispensation (Boateng & Afranie, 2020a). Apart from Turmann (2010) who looked at capacity development of chiefs and local government authorities with emphasis on the Royal Academy, its components and executing institutions, no further study has investigated why the Academy has not been operationalised and how in its absence, chiefs and local government authorities develop their capacity.…”
Section: Introductionmentioning
confidence: 99%